2020
DOI: 10.1136/oemed-2019-105962
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in a cohort of US firefighters from San Francisco, Chicago and Philadelphia: an update

Abstract: ObjectivesTo update the mortality experience of a previously studied cohort of 29 992 US urban career firefighters compared with the US general population and examine exposure-response relationships within the cohort.MethodsVital status was updated through 2016 adding 7 years of follow-up. Cohort mortality compared with the US population was evaluated via life table analyses. Full risk-sets, matched on attained age, race, birthdate and fire department were created and analysed using the Cox proportional hazard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(74 citation statements)
references
References 40 publications
4
69
1
Order By: Relevance
“…Furthermore, the impact of the healthy worker effect in the FDNY population may not allow our results to be generalizable to other WTC-exposed cohorts. While we found lower mortality than a study of non-WTC-exposed US firefighters, we suspect that some of the differences in SMRs from those of the FDNY may be explained, in part, by the earlier average year of hire and longer follow-up time since hire of the non-WTC-exposed US firefighters [ 28 ]. This indicates an older population that is farther from the point of workforce entry and therefore, likely to have experienced a diminution of the healthy worker effect, bringing their mortality rates closer to that of the US general population.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Furthermore, the impact of the healthy worker effect in the FDNY population may not allow our results to be generalizable to other WTC-exposed cohorts. While we found lower mortality than a study of non-WTC-exposed US firefighters, we suspect that some of the differences in SMRs from those of the FDNY may be explained, in part, by the earlier average year of hire and longer follow-up time since hire of the non-WTC-exposed US firefighters [ 28 ]. This indicates an older population that is farther from the point of workforce entry and therefore, likely to have experienced a diminution of the healthy worker effect, bringing their mortality rates closer to that of the US general population.…”
Section: Discussioncontrasting
confidence: 57%
“…Expected associations for well-established risk factors of premature mortality in our cohort provide confidence in our results. For example, SMRs of the cause-specific minor categories were overwhelmingly lower than expected compared with the general population, with the exception of non-significant but elevated rates of death from a building fire (SMR = 1.29), not surprising given that our population was nearly 89% firefighters, and mesothelioma (SMR = 1.71), which has been reported as elevated among firefighters compared with the general population [ 28 , 38 ]. Secondly, as was emphasized through SMR stratification by WTC-exposure, our cox proportional hazards analyses demonstrated that WTC-exposure intensity was not related to mortality risk while more typical risk factors such as being male, cigarette smoking, and older age conferred increased risk.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Breast cancer incidence was non-significantly elevated among men and among the 991 women included in the study and in both groups the increases were largest among those at younger ages (<65 years old for men and ages 50-55 for women (Daniels et al 2014)). In a published update adding 7 years of follow up to the pooled cohort, Pinkerton et al (2020) found that women firefighters had elevated mortality rates for bladder cancer and non-statistically elevated mortality from Non-Hodgkin's lymphoma, multiple myeloma, lung cancer and breast cancer (Pinkerton et al 2020). A study of Florida firefighters that included 5,000…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer incidence was non-significantly elevated among men and among the 991 women included in the study and in both groups the increases were largest among those at younger ages (<65 years old for men and ages 50-55 for women (Daniels et al 2014)). In a published update adding 7 years of follow up to the pooled cohort, Pinkerton et al (2020) found that women firefighters had elevated mortality rates for bladder cancer and non-statistically elevated mortality from Non-Hodgkin’s lymphoma, multiple myeloma, lung cancer and breast cancer (Pinkerton et al 2020). A study of Florida firefighters that included 5,000 women found elevated incidence of cervical and thyroid cancer and Hodgkin’s disease compared to the general Florida population (Ma et al 2006) and a more recent study of Florida firefighters using that state’s cancer registry found that women firefighters had elevated risk of melanoma, thyroid, and brain cancer (Lee et al 2020).…”
Section: Introductionmentioning
confidence: 99%